Augmented Reality dan Virtual Reality dalam Pembelajaran: Sebuah Tinjauan Sistematis tentang Pemahaman Konsep Peserta Didik - Neni Sriwahyuni; Muharleni (Journal of Social, Educational and Religious Studies, 2026)
The rapid advancement of digital technology has encouraged the integration of Augmented Reality (AR) and Virtual Reality (VR) as innovative learning tools capable of providing interactive and immersive learning experiences. However, the effectiveness of these technologies in enhancing conceptual understanding remains inconsistent across educational contexts. This study aims to comprehensively analyze the potential and limitations of AR and VR in learning, particularly regarding students’ conceptual understanding. A qualitative approach employing a Systematic Literature Review (SLR) method was adopted following the PRISMA 2020 guidelines. Data were collected from articles indexed in Scopus, Web of Science, ScienceDirect, SpringerLink, ERIC, and Google Scholar published between 2015 and 2025. Following the screening and selection process, 36 eligible articles were analyzed using thematic analysis. The findings reveal that AR and VR have significant potential to improve the visualization of abstract concepts, learning motivation, student engagement, and exploration-based learning experiences. Nevertheless, their impact on conceptual understanding is not always consistent and is strongly influenced by instructional design quality, pedagogical integration, learner characteristics, as well as infrastructure readiness and teacher competencies. Furthermore, challenges such as cognitive load, implementation costs, and digital access disparities remain significant barriers to the adoption of immersive technologies in education. This study highlights that the effectiveness of AR and VR depends not merely on technological sophistication but also on their integration with appropriate pedagogical strategies. Therefore, the development of more comprehensive AR- and VR-based learning models is necessary to support meaningful and sustainable conceptual understanding.